PEMBERLAKUAN SYARI’AH DALAM NEGARA BERAGAMA - Hukom, David Arthur (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2019)
Indonesia is a great country that is rich in natural resources, culture, tradition and religion. Religious diversity is a prosperity that is owned by Indonesia. Religious diversity that fails to be managed properly can cause problems and even damage the unity of the nation. It has to be well facilitated, and dialogue is one of the methods that can be used. The dialogue becomes a presentation of the diverse religions that brings peace in togetherness as one nation, peace that comes from a clear understanding and not a bias prejudice. It also will discuss many issues including the concept and principle of the Nation. The discussion about religion state is interesting especially the implementation of Shariah though it has not become a comprehensive law in all regions in this country, but in certain areas clearly brings its own color in our society. Shariah is not only talking about the interests of today, but also the spirit that has been maintained since the past. The spirit is not only talking about political memories from the past, but also the values of its believers. In fact, the implementation of Syariah does not run easly and sometimes it has to face more challenges and barriers but the spirit to make Syariah as a comprehensive law is need to be maintained. For one believes that human civilization can return to be a better life, back to early Islam which appeared and developed on earth. Aceh province is one of an example of Syariah implementation as a comprehensive law in society, eventhough it is not yet perfect, the Acehnese keep trying to make it as a guidance of shared life. This paper aims to point out Shariah as a great value to maintain a peace of life because there is an effort in dialouge between something ideal and real. Reality which does not support ideality does not become a barrier.